The impact of nationalism on civilisational development and human security: works of Said Nursi and Musa Jārullāh - Akhmetova, Elmira (International Institute of Advanced Studies (IAIS) Malaysia and Pluto Press (London), 2013)
This essay is an attempt to outline the ideology of nationalism, its types and impact on the well-being of societies from the viewpoints of two Muslim intellectuals, Said Nursi and Musa Jārullāh. Based on the predictions of these two scholars and the current political developments, it identifies the ideas of negative nationalism and racism to be one of the main reasons behind moral corruption, social, political and economic injustice prevalent in the modern world; and it offers some solutions to bring compassion, security, peace and harmony to humankind. The essay suggests that the universal principles of peace, fairness and virtue derived from the revealed religions can produce true civilisations, and offer true happiness and harmony to all members of the society regardless of their ethnic or ideological backgrounds. It also suggests that modern methods of studying political and social developments in the Muslim world should be urgently revised.